Large-Scale Transport Infrastructure Project Performance: Generating a Narrative of Context and Meaning - Love, Peter; Ika, L.A.; Matthews, Jane; Fang, W. (2021)
In this article, we go beyond the proverbial appreciation that context matters and provide a deep exploration of how and why it can help make sense of cost deviations in large-scale transport projects (>$500 million). Using abductive inference in combination with a multiple case study approach, the criteria of planning, funding, scope, contract, challenges/issues, and benefits are used to understand and interpret the context and meaning of project cost performance. By comparing two light rail transit systems and conducting an in-depth examination of a road project, this article examines the differences between procurement approaches and worldviews and how they can introduce bias into a project's cost performance outlook. The contributions of this research are threefold as it provides an avenue for a new line of inquiry to help better understand causal inferences, thus contributing to the development of a plausible theory of project cost performance; highlights the ambiguity associated with cost performance assessment and calls for the use of standardized definitions and terminologies so that evidence-based decision surrounding risk and uncertainty can be enacted; and suggests that by engaging in a collaborative benchmarking process of project completion data, the context and meaning of a project's performance can be documented.